The Role of Microteaching Course in Enhanching Pre-Service Teachers’ Self-Confidence During the Teaching Practice - Istiqomah, Annisa Nur; Karim, Sayit Abdul; Radjaban, R.Yohanes; Matas, Gordan (Universitas Pendidikan Mandalika, 2025)
Microteaching courses are crucial for equipping pre-service teachers with foundational skills through simulated teaching experiences before they enter actual classrooms. This mixed-methods study investigated how English Language Education Study Program (ELESP) pre-service teachers perceive the influence of microteaching courses on their self-confidence during PLP II teaching practice, and identified contributing factors. The study involved 27 ELESP pre-service teachers (9 male, 18 female) from Universitas Teknologi Yogyakarta, all of whom had completed microteaching courses and PLP II teaching practice. For the qualitative phase, six students were purposively selected for semi-structured interviews based on their high, middle, and low questionnaire scores, ensuring diverse perspectives on self-confidence during PLP II. Quantitative data was collected using a 4-point Likert Scale Scoring Rubric and analyzed, while qualitative interview data was analyzed using the interactive model adapted from Miles & Huberman (1994). Questionnaire results indicated that pre-service teachers' self-confidence related to microteaching courses in PLP II teaching practice was in a